The Turkish economy after the global economic crisis - Secil Pacaci Elitok; Thomas Straubhaar (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The Turkish economy has gone thru a fast and strong change in recent years. Three dimensions are of special significance: 1. Firstly, the Turkish economy has grown very quickly, with three severe recessions in 1994, 2000/1 and 2009. 2. Secondly, it has opened up rapidly but is still not that open as other economies with a similar level of development. 3. Thirdly, private business has increased but state enterprises or publicly owned and run firms are still important.
Keywords: 330